2010
DOI: 10.1016/j.pbi.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Accessing genetic diversity for crop improvement

Abstract: Vast germplasm collections are accessible but their use for crop improvement is limited-efficiently accessing genetic diversity is still a challenge. Molecular markers have clarified the structure of genetic diversity in a broad range of crops. Recent developments have made whole-genome surveys and gene-targeted surveys possible, shedding light on population dynamics and on the impact of selection during domestication. Thanks to this new precision, germplasm description has gained analytical power for resolvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
146
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(148 citation statements)
references
References 70 publications
2
146
0
Order By: Relevance
“…To facilitate the utilization of the database, web-pages are dynamically interfaced with it. This approach ensures that the information derived from the database is up-to-date (Glaszmann et al 2010). The DB allows two kinds of research: basic research, where it is possible to select the species and the list of accessions, and advanced research, in which all topics are shown.…”
Section: The Importance Of Results Disseminationmentioning
confidence: 99%
“…To facilitate the utilization of the database, web-pages are dynamically interfaced with it. This approach ensures that the information derived from the database is up-to-date (Glaszmann et al 2010). The DB allows two kinds of research: basic research, where it is possible to select the species and the list of accessions, and advanced research, in which all topics are shown.…”
Section: The Importance Of Results Disseminationmentioning
confidence: 99%
“…Crop genetic resources consist of the genetic diversity of germplasm that can be used in crop breeding programmes (Glaszmann et al, 2010) and can be organized into gene pools in accordance with the gene pool concept of Harlan and de Wet (1971). The primary gene pool of a crop consists of its own cultivars and landraces (and sometimes its wild progenitor), while the secondary gene pool consists of other related species from which agriculturally useful traits can be introgressed (Maxted et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This effort led to the founding of gene banks and collecting of genetic resources of crops and their wild relatives (Vavilov 1926). However, in spite of impressive numbers of collected accessions (estimated to be around 7 million worldwide), the loss of genetic diversity of species has been reported in many commercially important crops (Harlan 1975;Esquinas-Alcázar 2005;Glaszmann et al 2010). In the broadest sense, this alteration and narrowing of crop genetic diversity began with the first domestication of wild plants.…”
mentioning
confidence: 99%
“…In contrast, molecular markers accurately represent the underlying genetic variation and nowadays dominate genetic diversity research. Among the variety of markers to choose, retrotransposonbased and microsatellite markers (simple sequence repeats, SSRs) proved to be effective, thanks to their polymorphism and abundance in plant genomes (Glaszmann et al 2010). Microsatellites as highly informative codominant markers are used in population genetic research ranging from the level of individuals to closely related species.…”
mentioning
confidence: 99%